Biosurfactants as Potential Antitumor Agents - C. I., Ukaegbu; S. R., Shah; R. O., Alara; O. A., Thonda (Springer International Publishing, 2023)
Tumors are a solid mass of tissue that forms from the clustering of numerous abnormal cells. Many tumors are benign (non-cancerous) while most are malignant (cancerous). One common thing about tumors is that whether malignant or benign, they require treatment. However, the treatment approach differs for both classes of tumors. Although both types of tumors can affect different body parts (such as bones, skin, tissue, organs, and glands), special attention is mostly given to cancerous or malignant tumors because they are life-threatening and require special treatment. Chemotherapy and irradiation are currently the conventional treatment strategies for malignant tumors, but the problems of drug resistance and toxicity associated with tumor chemotherapy are driving the continued search for novel biocompatible antitumor agents as advocated by the World Health Organization. In this regard, natural products have received much research attention as an alternative and effective option for tumor management. Biosurfactants are natural compounds biologically produced by some strains of bacteria with potential application in different fields. Biosurfactants have attracted medical attention as promising molecules due to their diverse properties, versatility, and structural novelty. The medical field witnessed an increased commercial application of biosurfactants during the past decade because they are highly biocompatible, biodegradable, and exhibit low toxicity. The antioxidant, antibacterial, antiproliferative, and antiviral activities of biosurfactants make them relevant molecules for the treatment of many diseases, including tumors. Many types of biosurfactants such as surfactin, iturin, and fengycin lipopeptide have been produced from several Bacillus species and studied for antitumor activity by several scholars against breast cancer, colon cancer, leukemia, hepatoma, etc. These biomolecules are believed to significantly inhibit the proliferation of multiple tumor types by interfering with some tumor development processes. This chapter reviewed most of the previous studies on biosurfactants and their antitumor activities, focusing more on their potential mechanisms of action and possible grounds for advanced applications.